Derecho de la competencia y gobierno corporativo. Garantías de equidad frente a la integración regional, la liberalización comercial y la globalización económica - Rodríguez-Jaraba, Rafael (2011)
Regional integration, liberalization of trade, and economic globalization are not a temporary event of development. They form part of a new world order, and promise to expand the economy, encourage progress, slow down poverty, and reduce exclusion. Contrary to speculation, studies and mathematical evidence present them in this way; but their establishment must be gradual and scaled in order not to prejudice the protected sectors. The free market, as with all transforming processes, has its risks and can be perfected. Those who oppose the new world order reject its benefits and assure us that international prosperity compromises equality and the stability of poor nations. They say that the less developed countries are threatened by the domination of the trans-nationals. Moderate criticisms appreciate the transforming influx of the new world order, but refute its excessively superior attitude, and call for a process which advances more prudently and gradually. The right of competition and application of the principles of corporative government must be guarantees of equality on this new world stage.